Polymorphisms in the IL-6 and IL-6R receptor genes as new diagnostic biomarkers of acute appendicitis: a study on two candidate genes in pediatric patients with acute appendicitis - Sarsu, Sevgi Buyukbese; Yilmaz, Senay Gorucu; Bayram, Ali; Denk, Affan; Kargun, Kursat; Sungur, Mehmet Ali (Bmc, 2015)
Background: Acute appendicitis (AA) (OMIM: 107700) is an inflammatory disease which is characterized by appendiceal inflammation. Genetic and environmental factors contribute to the development of AA. Especially, multiple genetic factors appear to be promising in the explanation of etiopathogenesis of AA. IL-6 (Interleukin-6) is an inflammatory cytokine and IL-6 receptor (IL-6R) plays an important role in the immune response. IL-6 (-572G/C rs1800796) and IL-6R (1:G.154448302 T > C rs7529229) gene polymorphisms may have an impact on cytokine production, immune response and these gene polymorphisms may be used as inflammatory markers in the diagnosis of appendicitis. Method: A total of 75 children with appendicitis, and 75 healthy children were included in the study. DNA extracts were obtained from peripheral lymphocytes. Single-nucleotide polymorphisms (SNPs) were analysed using an automated SYBR (R) Green RT-PCR system in pediatric patients with appendicitis (n = 75) and healthy controls (n = 75). Results: The allele and genotype frequencies for IL-6 rs1800796 and IL-6R rs7529229 polymorphisms were not different between the study groups (p > 0.05). Any statistically significant differences as for age, sex and other laboratory factors were not detected between the patients with appendicitis for genotype-allele frequencies (p > 0.05). Still in analyses performed to determine correlations among age, and gender of the patients, routine laboratory parameters and allele-genotype frequencies, a statistically significant intergroup difference was not detected. Genotype and allele frequencies were consistent with Hardy-Weinberg equilibrium (HWE) in all groups. Discussion: This is the first study to investigate the effects of functional two polymorphisms on IL-6 and IL-6R genes in a pediatric patient group with AA risk. With this study we investigated the contribution of IL-6 (-572G/C rs1800796) and IL-6R (1:G.154448302 T > C rs7529229) polymorphisms on pathogenesis, and severity of AA in pediatric patients with AA: These results will guide further genetic researches to be performed on the role of IL-6 and IL-6R in AA. Conclusions: Given the putative biological importance of this SNPs, these emerging data can provide a new foundation to stimulate future debate and genetic investigations of AA, focusing on new molecular mechanisms such as other IL gene polymorphisms, particularly in accessible peripheral tissues for novel molecular diagnostics for appendicitis.
Keywords: Appendicitis; Interleukin-6; Interleukin-6 receptor; Polymorphism; Disease progression